2014
DOI: 10.4028/www.scientific.net/amm.613.390
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Rapid Prototyped Models with Using of FDM Technology

Abstract: Conventional technology are also today the main technology used for production of parts in mechanical engineering industry. In every machine shop we can see turning machines, milling machines, drilling machines and others. These machines are generally controlled by computers. But the modern production lines and production companies use also innovative technology to make production more effective, faster, less expensive. With regards of mentioned factors is possible to use also rapid prototyping technology, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…All samples in the previous, as well as in the current, research have the same basic shape with the dimensions shown in Figure 1 and were designed with respect to the possibilities of the technology and knowledge gained from the research in the precision of RP technology printing [5]. While in the previous tests the samples of this shape and dimension were exclusively printed, in this case some samples were assembled into these shapes.…”
Section: Test Patternmentioning
confidence: 97%
“…All samples in the previous, as well as in the current, research have the same basic shape with the dimensions shown in Figure 1 and were designed with respect to the possibilities of the technology and knowledge gained from the research in the precision of RP technology printing [5]. While in the previous tests the samples of this shape and dimension were exclusively printed, in this case some samples were assembled into these shapes.…”
Section: Test Patternmentioning
confidence: 97%
“…The design of the internal structure was executed in Creo 2.0 software [5], where the solid material in the thickness matching multiples of the contour width was clearly defined and subsequent setting of the number of contours in the Insight software for printing achieved the required printing trajectory to obtain higher strength in the direction of the acting tensile forces. The internal structure of the samples was designed with respect to the technological possibilities and findings gained from research into RP printing technology precision [6,7]. The printing parameters of individual samples are shown in Tab.…”
Section: Test Patternmentioning
confidence: 99%
“…3) from two materials with different internal printing structures. The samples were designed taking into account technological requirements and findings obtained from examination of RP printing precision [6].…”
Section: Introductionmentioning
confidence: 99%